Sosialisasi Manajemen Keuangan Digital bagi Pelaku Usaha dan Masyarakat di Kabupaten Tangerang - Basuki, Sucipto; Goestjahjanti, Francisca Sestri; winanti, winanti; Purno, Marhaendro; Himmy'azz, Istajib Kulla Kulla; Kumoro, Dwi Ferdi Cahya; Hasna, Shofwatun; Nurasiah, Nurasiah; Kamar, Karnawi; Adiyanto, Adiyanto; Jubaedah, Ida (IAHN Gde Pudja Mataram, 2024)
Business actors who still carry out many conventional financial transactions that have the risk of being lost and inviting criminals. The purpose of this socialization is to provide understanding and education to MSME actors to use and manage finances digitally. The method used is through lectures and interactive discussions. The results of the socialization can provide awareness to business actors to use digital finance in all financial transactions. Monitoring and evaluation are carried out by asking several participants directly about the socialization activities from the beginning to the end of the event. Making final reports and journals as a form of accountability for activities